Predicting behavior in extinct reptiles from quantitative analysis of trigeminal osteological correlates - Lessner, Emily J.; Xu, Xing; Young, Bruce A.; Echols, M. Scott; Jones, Marc E. H.; Elsey, Ruth M.; Holliday, Casey M. (Frontiers in Amphibian and Reptile Science, 2024)
Introduction Vertebrate sensory systems are in close contact with surrounding tissues, often leaving bony signatures behind. These bony features are the keys to assessing variation in sensory systems in fossil taxa. The trigeminal sensory system (e.g., trigeminal ganglion, ophthalmic, maxillary, and mandibular divisions) has osteological correlates throughout the skull, including the braincase (e.g., trigeminal fossa, prootic notch, ophthalmic and maxillomandibular foramina) and rostrum (e.g., mandibular canal, neurovascular foramina). Methods Here we measured and compared these features among a morphologically, phylogenetically, and ecologically diverse sample of sauropsids to determine strength of osteological correlates and to explore ecomorphological trends. We determined several suitable osteological correlates for trigeminal soft tissue features and discounted foramen count alone as a suitable osteological correlate. However, when size was accounted for, foramen count becomes a useful indicator of sensory ecology. Results and discussion Among extant taxa, those engaging in tactile sensory behaviors with the face exhibit relatively larger trigeminal tissues and osteological correlates than those not engaging in tactile sensory behaviors. Though patterns are unclear among several clades, both relative feature sizes and models used to predict sensory capacity reveal a trend of increasing tactile sensitivity along the pseudosuchian lineage. Overall, a quantitative assessment of ecomorphological trends of trigeminal osteological correlates proves informative for the hypotheses of sensory behavior in extinct taxa and supports the use of similar assessment methods for other osteological correlates.